Presidential elections and party system institutionalization in Brazil - Borges, André (2018)
In this article, I propose to analyze party system institutionalization in multiparty presidential countries in terms of the stability of the alliances made by parties to elect the president and form governments, and in terms of the coherence of parties’ strategies across the electoral and governing arenas. I argue that institutionalization is likely to increase as the parties that comprise the system interact in predictable ways, by forming large pre-electoral coalitions to dispute the presidency and these coalitions, in turn, provide voters with clear and distinctive government alternatives. I extend and complement the three dimensions of party system closure developed by Mair (1996;2002) and Casal-Bértoa and Enyedi (2016) by incorporating a set of measures to account for the degree of congruence between the structure of presidential competition and the formation of governments, and for the stability of interparty interactions in the presidential arena. The article relies on an in-depth case study of Brazil’s party systems that emerged during the post-1985 and the 1946-1964 democratic periods to examine these various dimensions of party system institutionalization.